Efficacy of Gemigliptin Add-on to Dapagliflozin and Metformin in Type 2 Diabetes Patients: A Randomized, Double-Blind, Placebo-Controlled Study (SOLUTION) - Lee, Byung Wan; Min, KyungWan; Hong, Eun-Gyoung; Ku, Bon Jeong; Kang, Jun Goo; Chon, Suk; Lee, Won-Young; Park, Mi Kyoung; Kim, Jae Hyeon; Kim, Sang Yong; Song, Keeho; Yoo, Soon Jib (Endocrinology and metabolism (Seoul), 2023)
Background: This study evaluated the efficacy and safety of add-on gemigliptin in patients with type 2 diabetes mellitus (T2DM) who had inadequate glycemic control with metformin and dapagliflozin.Methods: In this randomized, placebo-controlled, parallel-group, double-blind, phase III study, 315 patients were randomized to receive either gemigliptin 50 mg (n=159) or placebo (n=156) with metformin and dapagliflozin for 24 weeks. After the 24-week treatment, patients who received the placebo were switched to gemigliptin, and all patients were treated with gemigliptin for an additional 28 weeks.Results: The baseline characteristics were similar between the two groups, except for body mass index. At week 24, the least squares mean difference (standard error) in hemoglobin A1c (HbA1c) changes was –0.66% (0.07) with a 95% confidence interval of –0.80% to –0.52%, demonstrating superior HbA1c reduction in the gemigliptin group. After week 24, the HbA1c level significantly decreased in the placebo group as gemigliptin was administered, whereas the efficacy of HbA1c reduction was maintained up to week 52 in the gemigliptin group. The safety profiles were similar: the incidence rates of treatment-emergent adverse events up to week 24 were 27.67% and 29.22% in the gemigliptin and placebo groups, respectively. The safety profiles after week 24 were similar to those up to week 24 in both groups, and no new safety findings, including hypoglycemia, were noted.Conclusion: Add-on gemigliptin was well tolerated, providing comparable safety profiles and superior efficacy in glycemic control over placebo for long-term use in patients with T2DM who had poor glycemic control with metformin and dapagliflozin.